Diffusion MRI abnormalities in adolescent rats given repeated mild traumatic brain injury. Issue 12 (17th October 2018) - Wortman, Ryan C.; Meconi, Alicia; Neale, Katie J.; Brady, Rhys D.; McDonald, Stuart J.; Christie, Brian R.; Wright, David K.; Shultz, Sandy R.
Abstract: Objective: Mild traumatic brain injury (mTBI) is a serious health concern in the adolescent population. Repeated mTBI may result in more pronounced deficits, and has been associated with long‐term neurological consequences including neurodegeneration. As such, there is a critical need for the development of objective mTBI biomarkers to help guide medical management. Diffusion‐weighted imaging (DWI) is an advanced magnetic resonance imaging (MRI) technique that may detect brain abnormalities after mTBI. Diffusion tensor imaging (DTI) is the most commonly applied DWI method, and initial studies have reported DTI changes in mTBI patients. Furthermore, new DWI methods (e.g., track‐weighted imaging; TWI) are being developed that may also be sensitive to mTBIs, but remain to be comprehensively studied. Methods: This study utilized the Awake Closed Head Injury (ACHI) model of mTBI to investigate changes in DTI and TWI following repeated mTBI in adolescent male and female rats. A total of four ACHI impacts, two/day over two consecutive days, were delivered beginning on postnatal day 25. At 1 day and 7 days postinjury, rats were euthanized and brains were collected for DWI analyses. Results: Rats given repeated mTBI displayed changes in fractional anisotropy and radial diffusivity (i.e., DTI measures), as well as track density (i.e., TWI). Interpretation: These findings are consistent with initial DTI findings in mTBI patients, suggest that TWI may complement DTI, support the utility of DWI measures as biomarkers in mTBI, and further validate the ACHI rat model of mTBI.